Analyzing lipid profiles and dyslipidemia prevalence in hypertensive patients: a cross-sectional study from primary community health institutions - Wang, Wenxin; Li, Xinmin; Lv, Deliang; Wu, Xiaobing; Xie, Fengzhu; Xie, Wei; Wang, Jinxiao; Zhao, Zhiguang (Frontiers in Medicine, 2024)
Background A significant proportion of hypertensive patients also suffer from comorbid dyslipidemia, which critically influences their treatment outcomes and overall prognosis. Given its implications, the lipid profiles of hypertensive individuals warrant increased attention for more effective clinical management. Methods We analyzed data from 92,443 hypertensive patients registered at primary community health institutions in 2021. Employing a cross-sectional study design, we assessed the distribution of lipid levels and the prevalence of various dyslipidemia subtypes. Stepwise forward logistic regression was used to identify factors associated with dyslipidemia, adjusting for gender, age, body size, and other relevant characteristics. Results According to the 2023 Chinese Guidelines for the Management of Lipids, the overall prevalence of dyslipidemia was 37.5%. Subtype analysis revealed prevalence of high total cholesterol (TC) at 11.2%, high triglycerides (TG) at 16.0%, low high-density lipoprotein cholesterol (HDL-C) at 16.0%, and high low-density lipoprotein cholesterol (LDL-C) at 10.2%. TG abnormalities were more common among males (16.8%), whereas TC abnormalities predominated in females (14.4%). Notably, hypertensive patients with diabetes had higher levels of TG compared to non-diabetics (p = 0.009). Those with stroke and liver disease comorbidities exhibited lower TG levels than their counterparts (p = 0.018 and p < 0.001, respectively). Additionally, HDL-C levels were significantly lower in hypertensives with diabetes, coronary artery disease, and central obesity (p < 0.001, p = 0.026, p < 0.001, respectively). Regression analysis indicated that dyslipidemia prevalence correlates significantly with gender, age, diabetes, coronary heart disease, stroke, family history of hypertension, body mass index (BMI), central obesity, frequency of physical activity, smoking status, regular alcohol consumption, and abdominal ultrasound findings. Conclusion Our study underscores the necessity of rigorous lipid monitoring and analysis of dyslipidemia-influencing factors for the development of effective health management strategies within the community. There is a critical need to examine lipid profiles comprehensively and implement targeted therapeutic interventions aimed at managing hyperlipidemia, a modifiable risk factor for cardiovascular disease.